The Undergraduate to Graduate Medical Education Transition as a Systems Problem: A Root Cause Analysis. (20th January 2023) - Swails, Jennifer L.; Angus, Steven; Barone, Michael A.; Bienstock, Jessica; Burk-Rafel, Jesse; Roett, Michelle A.; Hauer, Karen E.
Abstract : The transition from undergraduate medical education (UME) to graduate medical education (GME) constitutes a complex system with important implications for learner progression and patient safety. The transition is currently dysfunctional, requiring students and residency programs to spend significant time, money, and energy on the process. Applications and interviews continue to increase despite stable match rates. Although many in the medical community acknowledge the problems with the UME-GME transition and learners have called for prompt action to address these concerns, the underlying causes are complex and have defied easy fixes. This article describes the work of the Coalition for Physician Accountability's Undergraduate Medical Education to Graduate Medical Education Review Committee (UGRC) to apply a quality improvement approach and systems thinking to explore the underlying causes of dysfunction in the UME-GME transition. The UGRC performed a root cause analysis using the 5 whys and an Ishikawa (or fishbone) diagram to deeply explore problems in the UME-GME transition. The root causes of problems identified include culture, costs and limited resources, bias, systems, lack of standards, and lack of alignment. Using the principles of systems thinking (components, connections, and purpose), the UGRC considered interactions among the root causes and developed recommendations to improve the UME-GME transition. Several of the UGRC's recommendations stemming from this work are explained. Sustained monitoring will be necessary to ensure interventions move the process forward to better serve applicants, programs, and the public good.